Global Futures - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Global Futures aims to improve the capacity of the CGIAR centres to evaluate and prioritise research investments, and to support the decision-making of international development partners and national policymakers by giving those who work in agricultural development the kinds of information they need to make the best decisions to support small farmers so they can boost their yields, increase their income, and develop a better understanding of how to adapt to climate change.